Radial growth and climate responses of healthy versus decayed subalpine conifer trees in the southeastern Qinghai-Tibetan Plateau - Lingzhuo Luo; Wenzhi Wang; Zhehong Wu; Yong Su (Ecological Indicators)
The forest loss and degradation caused by tree heart rot presents an increasingly challenging issue for the protection and utilization of forest resources. Yet, it is questionable whether heartwood-decayed trees can still function on par with healthy trees. Here, using tree ring data, we established basal area increment (BAI) series of healthy and heartwood-decayed fir trees at four sites (Abies spectabilis in Bomi; A. georgei Orr in Deqin as well as the Sygera Mountain; A. fabri Craib in Yajiageng) in the southeastern Qinghai-Tibetan Plateau (QTP). We conducted a comparative analysis of the difference in the BAI, response to climate factors and elasticity under environmental stress between the healthy and decayed fir. The results show that, in QTP, fir susceptibility to decay is uncorrelated with growth rates. However, after decaying occurs in fir trees, their radial growth is restricted in warm and humid areas (i.e., at Bomi and Yajiageng). The average BAI of healthy fir is 70.32 % and 86.32 % higher than that of decayed fir in Bomi and Yajiageng respectively (p < 0.01), but no significant difference in Deqin and Sygera (p > 0.05). Moreover, healthy fir exhibits a more pronounced response to climatic conditions. Almost all BAI series of healthy and decayed fir in the southeastern QTP is positively correlated with the temperature and vapor pressure deficit. Under temperature stress, decayed fir trees are less resistant at three sites. This empirical study supports that there is no correlation between conifer trees’ radial growth rate and their likelihood of heartwood decay, and provides a compelling explanation for the constrained growth of decayed fir trees. Our findings can bolster the accurate assessment of carbon sinks and the conservation of forest resources in regions prone to high-decaying risks.